2020
DOI: 10.1111/jcmm.15694
|View full text |Cite
|
Sign up to set email alerts
|

Selective blocking of CXCR2 prevents and reverses atrial fibrillation in spontaneously hypertensive rats

Abstract: Atrial fibrillation (AF) is the most common type of cardiac arrhythmia and increases the risk for stroke, heart failure and death. However, current antiarrhythmic therapy has moderate efficacy and considerable risks. Thus, there is a need for effective and safe therapeutic drugs for AF. The atrial inflammatory response, oxidative stress and fibrosis are common pathological alterations in AF. 1 Increasing evidence indicates that inflammation and its related immune response play a crucial role in the initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…For example, Zhang et al (2020a) provided evidence that the expression level of CXCR2 and the number of CXCR2+ immune cells were markedly increased in the atria of angiotensin (Ang) II-infusion-induced AF models. The administration of CXCR2 inhibitor SB225002 or knockout of CXCR2 significantly reduced AF inducibility, duration, conduction abnormalities and atrial fibrosis in mice compared with the vehicle treatment (Zhang et al 2020a(Zhang et al , 2020b. Fan and Wei (2020) and Zou et al (2019) also identified upregulated CXCR2 as a hub node for AF patients after the PPI network analysis of the GSE79768 dataset.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Zhang et al (2020a) provided evidence that the expression level of CXCR2 and the number of CXCR2+ immune cells were markedly increased in the atria of angiotensin (Ang) II-infusion-induced AF models. The administration of CXCR2 inhibitor SB225002 or knockout of CXCR2 significantly reduced AF inducibility, duration, conduction abnormalities and atrial fibrosis in mice compared with the vehicle treatment (Zhang et al 2020a(Zhang et al , 2020b. Fan and Wei (2020) and Zou et al (2019) also identified upregulated CXCR2 as a hub node for AF patients after the PPI network analysis of the GSE79768 dataset.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, our microarray results discovered that chronic Ang II infusion induces mainly the activation of inflammatory chemokines, extracellular matrix-receptor interactions, and ubiquitin-proteasome system in the atrial tissue [ 7 ]. Indeed, the expression levels of several components of these signaling pathways, including CXCL1, CXCR2, and UCHL1, and the immunoproteasome catalytic subunits LMP10/PSMB10 and LMP7/PSMB8, are significantly upregulated in Ang II-infused atria and patients with atrial fibrillation, and play a critical role in the development of hypertensive atrial fibrillation in mice [ 7 , 11 , 12 , 20 , 21 ]. These previous data were further confirmed by time series analysis of proteome profiles in the same mouse model, and highlight that these genes are important regulators of atrial fibrillation development.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines are a large family of small, inducible, secreted proteins that bind to coupled GPCRs on target cells and have the ability to recruit leukocytes to sites of injury, which contributes to AF development [ 39 42 ]. For example, Zhang et al found that CXCL1/CXCR2 signaling could drive the infiltration of monocyte in atria accelerating atrial remodeling and AF after hypertension [ 42 ], while these effects could be mitigated by inhibiting CXCR2 with SB225002 (ref [ 41 ].). CXCL12/CXCR4 axis also involves in a diversity of pathological processes, such as homeostatic immune cell migration, inflammatory response, tissue repair, and cell survival, which is considered as an attractive therapeutic target both in cardiac and noncardiac diseases.…”
Section: Discussionmentioning
confidence: 99%